Thorium Energy for Net Zero Emission: the Opportunities, Challenges, and Legal Issues - Hermanus Wim Hapsoro (Eastasouth Institute, 2026)
The issue of Indonesia's reliance on fossil fuels as a primary energy source is a matter of significant concern, particularly in light of the nation's substantial energy demands. The necessity for novel energy sources that can serve as reserves for the country is therefore paramount. The recent discovery of the element thorium, a constituent of nuclear radioactive energy sources, has elevated it to a position of prominence in the realm of sustainable energy sources. To date, no nation has successfully implemented the use of thorium energy; however, numerous studies have been conducted to encourage its development. The present scientific article was prepared using a doctrinal research approach, based on a comprehensive review of the extant literature. The subsequent analysis and organisation of the data collected results in the formulation of structural ideas, which are then explicated through a descriptive-analytical framework. The results of the discussion on this topic concentrate on the evaluation of the potential of thorium as an energy source and the necessity of thorium regulation in Indonesian positive law. The development of thorium in the future is identified as a sustainable aspect that can contribute to the achievement of Indonesia Net Zero Emission.